Identifikasi Spesies Plasmodium Malaria Di Wilayah Kerja Puskesmas Desa Hanura Pesawaran Lampung - Prasetyo, Eko; Haryatmi, Dwi (Jurnal Analis Kesehatan, 2023)
Malaria is one of the causes of death and morbidity in children and adults in tropical countries. Malaria is caused by Protozoa of the genus Plasmodium, Plasmodium in humans consists of 4 species, namely Palsmodium falciparum, Palsmodium vivax, Palsmodium malariae and Palsmodium ovale. Pesawaran District is the area most commonly found with malaria, in 2017 there were 1,738 cases of malaria in the working area of the Hanura Health Center. The purpose of this study was to find out and identify Plasmodium malaria species that infect people in the work area of the Hanura Village Public Health Center, Teluk Pandan District, Pesawaran Regency, Lampung. This type of research is a descriptive survey research using cross-sectional methods using univariate data analysis. The data in this study were primary data, namely the results of Plasmodium identification in blood smears and in the form of patient demographic data (age, sex, education and behavior using mosquito nets or not). The results showed that out of 164 respondents, 22 patients found Plasmodium parasites. The identified Plasmodium vivax parasites were 20 people (90.9%) while for Plasmodium falciparum there were 2 people (9.1%). Plasmodium parasites identified at the age of 5-11 years (children) were 6 respondents (27.3%), in female sex there were 13 people (59.1%), at the elementary school level there were 15 people (68.2%), the behavior of not using mosquito nets was 12 people (54.5%). From the results of this study it can be concluded that Plasmodium parasites were found and identified that infect people in the work area at the Hanura Village Health Center, Teluk Pandan District, Pesawaran Regency